Sistem Informasi Pembelian dan Penjualan Aneka Minuman Pada UD. Rifar Jaya Bogor - Wicaksono, Sutarji; Arisawati , Ester (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2022)
UD. Rifar Jaya is a shop engaged in the sale of various kinds of drinks. In the sales process, UD. Rifar Jaya still uses a manual and simple system where the cashier still uses paper which will cause the evidence to be lost or damaged. During the process of checking the inventory items, they are still looking for one by one whose stock is out or only a little so that it will take a long time. The purpose of designing information systems for the purchase and sales of various beverages is to simplify the process of purchase and sales transactions in processing the data. The research method used is to collect some data including the method of observation, interviews, and literature studies to find out what problems are happening at UD. Rifar Jaya. The method of system development used is the waterfall method. With the creation of this desktop-based program, UD. Rifar Jaya is expected to be assisted in processing data on items, suppliers, customers, managing purchase and sales transactions, and making reports on items, purchases, and sales to be more effective and efficient.